What does the beck depression inventory measure in myocardial infarction patients? a psychometric approach using item response theory and person‐fit. Issue 2 (21st May 2015) - Wardenaar, Klaas J.; Wanders, Rob B.K.; Roest, Annelieke M.; Meijer, Rob R.; De Jonge, Peter
Abstract Observed associations between depression following myocardial infarction (MI) and adverse cardiac outcomes could be overestimated due to patients' tendency to over report somatic depressive symptoms. This study was aimed to investigate this issue with modern psychometrics, using item response theory (IRT) and person‐fit statistics to investigate if the Beck Depression Inventory (BDI) measures depression or something else among MI‐patients. An IRT‐model was fit to BDI‐data of 1135 MI patients. Patients' adherence to this IRT‐model was investigated with person‐fit statistics. Subgroups of "atypical" (low person‐fit) and "prototypical" (high person‐fit) responders were identified and compared in terms of item‐response patterns, psychiatric diagnoses, socio‐demographics and somatic factors. In the IRT model, somatic items had lower thresholds compared to depressive mood/cognition items. Empirically identified "atypical" responders (n = 113) had more depressive mood/cognitions, scored lower on somatic items and more often had a Comprehensive International Diagnostic Interview (CIDI) depressive diagnosis than "prototypical" responders (n = 147). Additionally, "atypical" responders were younger and more likely to smoke. In conclusion, the BDI measures somatic symptoms in most MI patients, but measures depression in a subgroup of patients with atypical response patterns. The presented approach to account for interpersonal differences in item responding could help improve the validity of depression assessments in somatic patients. Copyright © 2015 John Wiley & Sons, Ltd.